Product Design Optimization Training to Support Sales in E-Commerce - Athoillah, Fikri Aziz; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Rahmawati, Putri (Indonesian Journal of Community Empowerment (IJCE), 2025)
Factual problems in the field are that there are still some MSMEs who upload product photos with poor lighting, inappropriate backgrounds, and without considering design aesthetics and visual identity. This condition indicates the need for educational intervention in the form of training that can help business actors understand the importance of product design as well as basic technical skills such as taking product photos, using simple design applications, and effective visual design principles. The method used in this community service activity is a participatory educational approach through training activities and direct practice focused on improving participants' skills in designing and presenting products visually for digital marketing purposes. The results of the implementation of this community service activity identified that increasing the capacity of MSMEs in designing and presenting products more attractively on e-commerce platforms. An important lesson from this activity is that the digitalization of MSMEs does not always have to start from complex technological aspects, but can start from simple things but have a big impact, such as improving the visual quality of the product. Attractive product design can be an entry point to building a professional business presence in the digital world.